Physicochemical Characteristics of Bitter Leaf (Vernonia amygdalina Del.) Kombucha with Palm Sugar Addition - Bambang Dwiloka; Heni Rizqiati; Paras Lintang Adiwiratna; Aprilia Elok Kusumaning Hapsari; Novita Sintya Dewi (Diponegoro University, 2024)
Functional drinks are processed drinks that contain food components that are beneficial for body health and have good sensory evaluation. Functional drinks can be used to prevent degenerative diseases such as diabetes mellitus. Kombucha is a functional drink fermented from tea and sugar using a kombucha starter or Symbiotic Culture of Bacteria and Yeast (SCOBY). Kombucha has functions as an antioxidant, antidiabetic, anticancer and antimicrobial. A variety of leaves that include phenols and bitter leaves with components that are beneficial to the body can be used to make kombucha. Palm sugar can be used as alternative sugar for kombucha fermentation because palm sugar has a low glycemic index of 35. This study aims to determine the effect of using palm sugar concentration on total dissolved solids, viscosity, pH value, total flavonoids, total phenols, and reducing sugar content. The research results show that the use of palm sugar can increase total dissolved solids, viscosity, pH value, total flavonoids, total phenols and reducing sugars. The best treatment is the use of 25% palm sugar with a total soluble solids value of 18.38˚Brix, viscosity of 1.37 cP, pH value of 3.43, total flavonoids of 0.275 mg QE/g sample, total phenols of 0.99 mg GAE/ml, and reducing sugar of 9.24%.